The effect of customer service quality on customer engagement to use Indosat Ooredoo products: a case of Indosat Ooredoo Store Wahidin Cirebon - Erwan Iskandar; Sherin Monita; Ellin Herlina (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — To examine the influence of customer service quality on customer engagement to use Indosat Ooredoo products.Research method — This research employs a quantitative approach with simple linear regression analysis techniques. Primary data was obtained through distributing questionnaires. Samples in this study were 100 respondents from Indosat Ooredoo Store Wahidin Cirebon.Result — The findings indicated that customer service quality has a significant effect on customer decisions. R2 is called as the determinant coefficient which in this case is 51.2%. It can be interpreted that the influence of customer service quality reached 51.2% of on customer engagement at Indosat Ooredoo, while the remaining 48.8% is influenced by other factors.